Use of Ottawa ankle rules in a referral hospital in Peru - Palacios-Flores, M.A. (2022)
Objective: The aim of the study was to evaluate the validity and safety of Ottawa's ankle rules (OAR) in the urgency department of referral hospital in Peru. Materials and methods: An observational-transversal study was conducted for a duration of 5 months (April–June 2016). Target population were all patients older than 18 years with a foot and ankle injury who came to the urgency department. A convenience non-randomised sampling was used. The OAR test was applied and X-rays of the foot and/or ankle were performed in all patients who met the inclusion and exclusion criteria. The data obtained was analysed using the SPSS 20.0 software. Sensitivity, specificity, positive predictive value, negative predictive value and likelihood ratio positive and negative were calculated from statistical analysis. Results: A total of 428 patients were evaluated. The OAR test's sensitivity was 97.2%, specificity was 30.3%, positive predictive value was 22.0%, negative predictive value was 98.2%, likelihood ratio positive and negative were 1.39 and 0.09, respectively. With the application of the OAR test, a reduction of 31.2% of the total X-rays was evidenced, which could generate a saving of US $1165. Conclusions: In conclusion, OAR's validity and safety in our environment are comparable to international data, with a reduction in the unnecessary use of radiographs. Multicentric studies involving a larger sample and longer study time are necessary to protocolize OAR in emergency units.